Model berstruktur dalam hubungan sokongan sosial, kompetensi komunikasi dan pengurusan tanggapan dengan kesejahteraan psikolgi mangsa banjir - Nur Haffiza, Rahaman (2020)
Studies on aspects of social support, communication competency, impression management and psychological well-being among disaster victims have long been an interest of the Western researchers. However, studies on the effects of these variables in the context of disaster, especially flood disasters in Malaysia are still less focused on. In addition, several issues related to demographic aspects such as gender and income are also seen as less respected by researchers, particularly in the context of flood in Malaysia. Therefore, this study aims to identify the influence of social support, communication competency and impression management on the psychological well-being of the flood victims. In addition, this study also examines whether demographic factors such as gender and income have the potential to act as a moderator on the studied variables. Generally, this study uses quantitative methods in the process of data collection and analysis. A total of 300 questionnaires have been distributed to flood victims in the Kemaman district. Partial Least Square – Structural Equation Modelling (PLS-SEM) is used to test the hypotheses of the study. The result shows that the three variables of social support, communication competency and impression management have a significant impact in affecting the psychological well-being of the flood victims. Furthermore, the findings also revealed that the factor of gender is not a moderator between the three variables and the psychological well-being of the flood victims, in contrast of the factor of income, the result shows that the income is the moderator between the impression management and the psychological well-being of the flood victims. Hence, the findings conclude that social support, communication competency and impression management are important and should be emphasized in order to improve the psychological wellbeing of the flood victims. This study further explains the contributions of the study in order to improve the knowledge in the areas of communication and the strengthening of the Social Capital Theory.